A new species of grass mouse, genus Akodon Meyen, 1833 (Rodentia, Sigmodontinae) from central Peruvian Yungas - Jimenez Aguado, Carlos Francisco; Pacheco Torres, Victor Raul (THERYA, 2016)
The genus Akodon is one of the most abundant and species-rich genus of Neotropical mammals. Its species-level taxonomy has been changing actively since its establishment. Currently, the genus is divided into five groups of species: aerosus, boliviensis, cursor, dolores, and varius. Most taxonomic studies of the genus Akodon have focused on boliviensis, varius, and cursor. Taxa from the aerosus group, including A. orophilus, remain largely unknown and poorly studied, even when several authors indicate that most species could constitute species complexes. Here we review populations currently assigned to A. orophilus; our results allowed the description of a new species of Akodon. We carried out a complete and thorough revision of species of the Akodon aerosus group from the central Peruvian montane forests. We included external and craniodental characters and morphometric data for our analyses. Multivariate statistics and morphological characterizations were performed in order to find differences between species. A new species of Akodon from Peru is described based on combined analyses of cranial morphology and morphometric data. This new species was compared with other taxa from the aerosus species group, it is easily distinguishable from congeners by a unique combination of pelage coloration, body size, and cranial morphology. This new species is most likely endemic to montane forests from Huánuco, and its discovery contributes to uncover the real diversity of Peruvian rodents, adding up to nine species of Akodon from montane cloud forests. Moreover, it supports the previous hypothesis that montane rodent species are complex species; therefore, further research is necessary.